Problemy kodyfikacyjne polskiego prawa administracyjnego - Bieś-Srokosz, Paulina (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The codification of the law seems obvious when the legislator intends to unify the regulations of a given branch of the law. In the Polish legal system, each branch of the law has its own code, such as civil, criminal and administrative proceedings. However, the latter is not an example of the unification of all administrative law but only of its procedural part. In this article, the author tries to analyse the draft law on basic concepts of administrative law, which was to serve as an example of the administrative law code. It is difficult to state clearly whether the actual codification of the entire administrative law is possible, if only for the sake of its extensive regulation of every area of our life. An attempt to codify administrative law in Poland, unfortunately, has been unsuccessful for over a dozen years. The very ideas, i.e. the unification of regulations in the field of administrative law, and thus the grid of its basic concepts, should be considered legitimate and even necessary. There are several reasons for this position, for example, due to the impact of civil law on administrative law, which creates and functions in legal trading new legal institutions that have a hybrid character. As a consequence, this raises difficulties in the unambiguous classification of a given legal institution into a given branch of law.
Keywords: codification; administrative law; codification bill